EFFECT OF PK APPLIED FROM ORGANIC AND INORGANIC SOURCE ON THE PERFORMANCE OF POTATO UNDER RAINFED CONDITION IN SHIMLA HILLS - Sud, K. C.; Jatav, M. K.; Trehan, S. P. (Potato Journal, 2013)
Studies conducted on brown hill soils revealed positive effect of PK application through farmyard manure and inorganic fertilizers on total tuber yield, yield of large sized tubers as well as nutrients uptake by potato under rainfed conditions. Application of N enhanced protein content while FYM and K improved vitamin C content. Correlation matrix between leaf composition for N and K at critical growth stages showed the vital importance of these elements in potato production.